Hepatoprotective Effect of Aqueous Extract of Solanum macrocarpon Leaves against Carbon tetrachloride-Induced Liver Damage in Rats - Olusola Bolaji Adewale, Omotade Ibidun Oloyede, Amos Onasanya, Israel Idowu Olayide, Scholastica Onyebuchi Anadozie, Adewale Oluwaseun Fadaka (Journal of Applied Pharmaceutical Science, 2015)
Liver damage is a growing concern of today’s modern society. The increasing incidence of exposure to toxic agents has contributed to liver diseases. There is therefore need for hepatoprotective agents. This study was aimed at investigating the protective effect of aqueous extract of the leaves of Solanum macrocarpon against CCl4-induced liver damage in rats. Six groups of four animals each were used for the investigation. Group 1 served as control, groups 2, 3 and 4 animals were pre-treated with leaf extract of Solanum macrocarpon at 250mg/kg, 500mg/kg and 750mg/kg body weight respectively for 14 days prior to a single intraperitoneal administration of CCl4. Animals in groups 5 and 6 received only the extract at a dose of 750mg/kg body weight and CCl4 respectively. All animals were sacrificed 24 h after the administration of CCl4. The liver functions tests were performed in addition to their histopathological evaluation. Results obtained showed significant adverse changes in the levels of all measured parameters in CCl4 treated rats. However, pre-treatment with aqueous extract of S. macrocarpon prevented the adverse changes. Our findings suggest that S. macrocarpon protects the liver against CCl4-induced damage. This could be attributed to the presence of phytochemical compounds in the plant.
Keywords: Carbon tetrachloride,Chemoprotective, Hepatoprotective, Phytochemical, Solanum macrocarpon.